Intensive weight loss combining flexible dialysis with a personalized, ad libitum, coach‐assisted diet program. A "pilot" case series. Issue 3 (12th December 2014) - Vigotti, Federica Neve; Teta, Luigi; Pia, Anna; Mirasole, Sara; Guzzo, Gabriella; Giuffrida, Domenica; Capizzi, Irene; Avagnina, Paolo; Ippolito, Davide; Piccoli, Giorgina Barbara
Abstract Obesity is a growing problem on dialysis. The best approach to weight loss has not been established. The risks of malnutrition may offset the advantages of weight loss. Personalized hemodialysis schedules, with an incremental approach, are gaining interest; to date, no studies have explored its potential in allowing weight loss. This case series reports on combining flexible, incremental hemodialysis, and intensive weight loss. Setting: a small Dialysis Unit, following incremental personalized schedules (2–6 sessions/week, depending on residual function), tailored to an equivalent renal clearance >12 mL/min. Four obese and two overweigh patients (5 male, 1 female; age: 40–63 years; body mass index [BMI] 31.1 kg/m2) were enrolled in a coach‐assisted weight loss program, with an "ad libitum" approach (3–6 foods/day chosen on the basis of their glycemic index and glycemic load). The diet consists of 8 weeks of rapid weight loss followed by 8–12 weeks of maintenance; both phases can be repeated. This study measures weight loss, side effects, and patients' opinions. Over 12–30 months, all patients lost weight (median −10.3 kg [5.7–20], median ΔBMI–3.2). Serum albumin (pre‐diet 3.78; post‐diet 3.83 g/dL), hemoglobin (pre‐diet 11; post‐diet 11.2 g/dL), and acid–base balance (HCO3 pre‐diet: 23.3; post‐diet: 23.4 mmol/L) remained stable, with decreasing needs for erythropoietin and citrate or bicarbonate supplements. Calcium‐phosphate‐parathyroid hormone (PTH) balance improved (PTH‐pre 576; post 286 pg/mL). Three out of 4 hypertensive patients discontinued, 1 decreased antihypertensives. None experienced severe side effects. Patient satisfaction was high (9 on a 0–10 analog scale). Personalized, incremental hemodialysis schedules allow patient enrollment in intensive personalized weight loss programs, with promising results.